Penggunaan Modul “Barus Bandar Kuno di Pantai Barat Sumatera” pada Mata Pelajaran Sejarah di Kelas X SMA Erlangga Pematangsiantar - Ahmad Fakhri Hutauruk; Andres M. Ginting; Ahmad Arif Budiman Nasution (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This research aims to find out the opinions of teachers and students about the use of modules in historical learning at Erlangga Pematangsiantar High School. This type of research is descriptive-qualitative. Data was taken from the informant of 1 history teacher, 28 students consisting of 15 students of class X IPA and 13 students of class X IPS and Principal through observation, interview, and documentation techniques. The validity of the data in this study is tested using data triangulation techniques, then the collected data is analyzed data reduction, data presentation, and conclusion withdrawal, so that the modules are made effective then the teacher must refer to the theory put forward by Everett M. Rogers in which the module has excellence, consistency, complexity, can be tested and can be observed. From the results of the research it can be concluded that modules made by teachers of history subjects are effective.